Shwachman-Diamond syndrome - etiology, symptoms, diagnosis, treatment, prognosis - Kwaśniewska, Paulina Klaudia; Chmura, Katarzyna; Zimnoch, Barbara; Rendaszka, Katarzyna; Kowalska, Katarzyna; Pyziołek, Marta; Bonarska, Marta; Stróżna, Małgorzata; Najbar, Joanna Monika (Quality in Sport, 2026)
Shwachman–Diamond syndrome (SDS) is a rare inherited disorder with exocrine pancreatic insufficiency, bone marrow dysfunction, and skeletal anomalies. Most cases result from biallelic SBDS mutations, though variants in EFL1, DNAJC21, and SRP54 are reported. Patients present with diarrhea, neutropenia, infections, growth delay, and skeletal abnormalities. Diagnosis combines clinical assessment, lab tests, pancreatic function, bone marrow analysis, and genetic confirmation. Management is supportive, including pancreatic enzymes, nutrition, infection prevention, and hematologic monitoring. Hematopoietic stem cell transplantation is reserved for severe marrow failure or malignancy. Prognosis depends on hematologic involvement, but early recognition and multidisciplinary care improve outcomes. Introduction SDS is a rare ribosomopathy presenting in infancy with pancreatic insufficiency, neutropenia, and skeletal anomalies. SBDS and related gene mutations disrupt ribosome biogenesis, increasing the risk of marrow failure or malignancy. Purpose To summarize SDS genetics, clinical features, diagnosis, and management, highlighting current and emerging therapies. Material and Methods A systematic review of PubMed, MEDLINE, Scopus, and Web of Science (1964–2024) used keywords “Shwachman–Diamond syndrome,” “SBDS,” “ribosomopathy,” and “bone marrow failure.” Studies on genetics, clinical features, diagnosis, or management were included. Discussion SDS is genetically and clinically heterogeneous. Diagnosis integrates clinical, lab, and genetic data. Management is supportive, with HSCT for severe marrow failure or malignancy. Early diagnosis and multidisciplinary care improve outcomes, while emerging molecular therapies may provide future options.